Individualized Approaches to Diabetes Care in Nursing Homes - Sughra Majeed, Razia Sultana, Amtul Shakeel, Nadia Ashraf, Farhat Perveen, Sadia Rafique (Pakistan Journal of Medical & Health Sciences, 2022)
Although diabetes care has been widely established as a single entity, data in older, frail individuals with numerous comorbidities and have limited polymedication. This group accounts for a sizable number of nursing home residents (NHs). We came together as a group of experts with multidisciplinary (endocrinologists, geriatricians, Nurses staff, general practitioners and diabetologists) with real-world practice in this field, which is becoming more and more important globally, to compile practical, straightforward guidance on the managing of senior, fragile patients of diabetes. An Individual Care Plan (ICP), which is presented in layman’s terms, is the cornerstone of a patient’s diabetes treatment. This is due to the demands placed on personnel of NH (medical coordinator, manager, nurses, and caregiver working at the front lines, and the other caregiver worker which is under training). The actual purpose of this document, which is released when the patient is admitted, is to made prescriptions ensure that given at and followed after admission. It details the need for proper treatment, regular monitoring, and dates and times for essential examinations and testing. This entails keeping tabs on the patient’s HbA1c, as well as their blood and urine glucose levels and any complications that may arise from the condition (hypoglycemia, cardiovascular disease, foot disorders, ocular problems, malnutrition, kidney failure and peripheral neuropathy). Consequentially, staff education on the unique challenges of care for an elderly person with diabetes, emergency procedures, and maintaining an up-to-date ICP for use by medical professionals is essential. Keywords: Diabetes care, nursing home, staff nurses